A regulação do sistema agroalimentar brasileiro pela agricultura familiar: a desburocratização do comércio de alimentos, a gestão democrática dos recursos agrícolas e a implementação de órgão com poder normativo para a efetivação da alimentação adequada - Sousa, Marana Sotero de (2022)
The agri-food crisis present throughout the world is not a current fact and is gradually worsening in the global system of economic governance. The subject in question, as it involves the human right to adequate food, family farming and questions about the effective regulation of the Brazilian agrifood system, seeks to achieve, in addition to food security and food sovereignty itself, and adequate food, to go through theoretical-doctrinal systematizations and concepts of human, agro-environmental and economic rights. In this way, this research presents the following question: is it possible to carry out a regulation of the Brazilian agri-food system by family farming, in order to provide, in addition to the debureaucratization of the trade in food from family production, also the democratic management of agricultural resources from the implementation of a body with normative power for the implementation of adequate food, food security and food sovereignty? In this context, understanding the Brazilian rural sector associated with family farming as promoters of the sustainability of the Brazilian rural environment and the food market is relevant. Still, pondering the idea of democratic management of agricultural resources for food with a view to food security and sovereignty are inseparable factors from the topic in question. Thus, a general objective was outlined, in order to highlight the need to review the regulation of the agri-food system, as well as specific and attentive legislation to reduce bureaucracy in trade arising from agricultural food production. Enrique Leff's idea of organicity of Environmental Rationality is adopted as a theoretical framework and method, from which it tries to deconstruct the power strategies of market rationality, articulating the sciences through a dialogue of knowledge, at the same time as extols productive practices and ethical styles in the use of nature. Environmental rationality tries to combine the theoretical and instrumental order of knowledge with the values of peasant, traditional, indigenous and quilombola communities, which constitute environmental knowledge which values traditional knowledge. Following this method, the work presents segments that mix the legal and sociological approaches extracting data mostly qualitative from the various studies relevant to the subject in question, being equally necessary the analysis of information and quantitative obtained through periodicals and dossiers on the range of agricultural and environmental resources present in Brazil, which directly or indirectly are aimed at achieving food security and adequate food, analyzing them, concomitantly, from the perspective of family farming, as well as regarding the existence of regulatory instruments and of legislation in the national legal system on food that are guided by the guidelines f family farming. The hypothesis is the one that envisions the possibility and feasibility of creating a regulatory instrument with powers and normative force, in a way that allows the realization of adequate food and food security and sovereignty, both through the reduction of bureaucracy in the commercialization of products from agriculture family, as well as through the regulation of the current Brazilian agri-food system, inserting in it the participation and interests of the family farming category, aiming for the family farming segment to carry out a democratic management of agricultural resources and, with that, it is possible to achieve a oriented primarily by the principles, traditions and knowledge of family farming.